La gestión del marketing y la incidencia en las ventas del almacén de ropa “BEBITOS” en la ciudad de Riobamba - Albán Erazo, Evelyn Gabriela (2025)
The main objective of this resecrh study was to focus on the marketing management and the impact on the sales of the clothing store "Bebitos" in the city of Riobamba, is a research work based on analyzing the marketing management and the strategies applied in the children's clothing store, and how these strategies influence sales. The clothing store Bebitos is dedicated to the marketing of clothing and accessories for children from 0 to 14 years since 2008, becoming one of the pioneering children's clothing stores in the city. The "Bebitos" store has experienced a significant decline in sales in recent periods. This commercial decline has generated concern among the shop's owners, who have observed a negative trend that directly affects the shop's financial viability and competitive position in the local market. One of the possible causes identified for the drop in sales is that the marketing management being applied is not adequate, which, so far, has been mainly based on empirical knowledge, which has relied heavily on intuition and has been lacking in the marketing strategies that have been applied. Since its opening, empirical marketing techniques have been used because they were sufficient to start the business, however; during the last few years the Bebitos store has decreased its sales. Likewise, they should improve their advertising, to make their products known and achieve a greater participation in the market and take advantage of the technological resources that currently exist and exploit them to achieve a benefit for them and their customers. For the present investigation the hypothetical deductive method was handled based on the resolution of a business problem, through the collection of data and its exegesis in the statistical software SPSS 2021, and the interpretation of the hypotheses raised by the researcher through the Chi-square method, which showed that if there is relativity between the variables raised, therefore if it affects the sales of the store "Bebitos", with its marketing management, consequently the application of marketing strategies are important, because it can cause great advances in the store or great delays in its growth and permanence in the Riobambeño market.